2023
DOI: 10.3389/fendo.2023.1220516
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sodium–glucose cotransporter-2 inhibitors and muscle atrophy in patients with type 2 diabetes mellitus: a systematic review and meta-analysis

Chengdong Xia,
Yufeng Han,
Chunhui Yin
et al.

Abstract: AimThis study aims to assess the association between sodium–glucose cotransporter type-2 inhibitor (SGLT-2i) treatment and muscle atrophy in patients with type 2 diabetes mellitus (T2DM).MethodsWe searched six databases from 1 January 2012 to 1 May 2023, without language restrictions. The primary outcome was muscle. Secondary outcomes were weight loss, weakness, malaise, or fatigue. Subgroup analyses were performed according to different definitions of muscle, treatment duration, and measurement methods. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Other limitations of treatment may include the requirement for regular monitoring of blood pressure and volume status [ 5 ]. SGLT-2is may also be associated with muscle atrophy, and as T2D is a further risk factor for sarcopenia, patients should be assessed for other relevant risk factors, such as age, weight, and muscle mass when considering this type of treatment [ 65 ].…”
Section: Comparison Of Current Clinical Management For T2d and Ckd Ve...mentioning
confidence: 99%
“…Other limitations of treatment may include the requirement for regular monitoring of blood pressure and volume status [ 5 ]. SGLT-2is may also be associated with muscle atrophy, and as T2D is a further risk factor for sarcopenia, patients should be assessed for other relevant risk factors, such as age, weight, and muscle mass when considering this type of treatment [ 65 ].…”
Section: Comparison Of Current Clinical Management For T2d and Ckd Ve...mentioning
confidence: 99%
“…Sodium-glucose cotransporter 2 inhibitors that decrease proximal tubular glucose reabsorption, not only reduce body weight and body fat, but meta-analyses have indicated that they also reduce lean body mass and skeletal muscle mass. 25,26 Sodiumglucose cotransporter 2 itself is not present in skeletal muscle, and its effects on skeletal muscle may be mediated by indirect systemic effects. Possible mechanisms include decreased uptake of glucose and amino acids and increased degradation of muscle proteins in skeletal muscle associated with decreased insulin secretion, but the detailed mechanisms remain unclear (Tables 2 and 3).…”
Section: Glucose-lowering Drugsmentioning
confidence: 99%
“…Sodium–glucose cotransporter 2 inhibitors that decrease proximal tubular glucose reabsorption, not only reduce body weight and body fat, but meta‐analyses have indicated that they also reduce lean body mass and skeletal muscle mass 25,26 . Sodium–glucose cotransporter 2 itself is not present in skeletal muscle, and its effects on skeletal muscle may be mediated by indirect systemic effects.…”
Section: Drugs That Cause a Certain Frequency Of Sarcopenia Or Myopathymentioning
confidence: 99%